Sosialisasi Kampus Tangguh Bencana Socialization of Disaster Resilient Campus - Sukaaro Waruwu; Desirima Zega; Herdi Narto Harefa; Fajar Iman Mendrofa; Sevra Juliana Zebua; Hatinurani Telaumbanua; Erni Yanti Hia (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Indonesia, as a nation with exceptionally high disaster vulnerability due to its geographical and geological conditions situated at the convergence of three active tectonic plates, necessitates comprehensive mitigation efforts involving all societal elements, including higher education institutions. The Nias region, which possesses an extensive history of various natural disasters, requires particular attention in disaster preparedness initiatives. This research aims to analyse the implementation of the Disaster-Resilient Campus socialisation programme at the Faculty of Economics, Universitas Nias, to enhance the capacity of academic community members in confronting disaster risks. The implementation methodology encompasses training and workshops conducted by resource persons from the National Disaster Management Agency (BNPB) and regional disaster management agencies (BPBD), evacuation simulations featuring earthquake and campus fire scenarios, development of emergency Standard Operating Procedures (SOPs), and continuous monitoring and evaluation processes. The activities were conducted over two days, actively involving students, lecturers, and educational personnel throughout the entire programme sequence. Research findings demonstrate that 92% of participants experienced significant improvement in understanding disaster mitigation and emergency response procedures. Emergency SOP documents were successfully compiled and disseminated throughout the faculty environment as standard emergency procedure guidelines. Evacuation simulations proved highly effective, achieving evacuation speed improvements of up to 50% compared to initial baseline measurements. The programme successfully fostered a disaster-aware culture, evidenced by the autonomous formation of student disaster response volunteer teams. The implementation of the Disaster-Resilient Campus programme demonstrates effectiveness in establishing adaptive and responsive preparedness governance systems for disaster risks within higher education environments.